Investigating multimedia-aided teaching (MAT) in ESP class: A case study from Sharia Business Law course - Pujiati, Tri; Arjulayana, Arjulayana (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Many studies have shown a gradually changed in teaching strategy from conventional to digital classrooms. However, little is about multimedia-aided teaching (MAT) enactment in teaching English for specific purposes (ESP) for Sharia Business Law students in understanding Sharia Business Law terms. This study aims to investigate the use of MAT to improve student's understanding of Sharia Business Law terms. This case study involved 48 students who took an English for Business Law course in the fifth semester at a university in East Java, Indonesia. Data were garnered through observation, questionnaires, and interviews. The quantitative data were analyzed using descriptive statistical analysis, while the qualitative data were analyzed using thematic analysis. The findings show that the students were more enthusiastic about learning ESP by using MAT, and the learning materials and visualization of multimedia (PPT and picture) are interesting. In addition, MAT is effective for teaching ESP in Sharia Business Law courses. This study implies how MAT is used to help the students improve their understanding of the terms of Sharia Business Law.